Improved Early Postoperative Range of Motion in Total Knee Arthroplasty Using Tranexamic Acid: A Retrospective Analysis - Dorweiler, Matthew A.; Boin, Michael A.; Froehle, Andrew W.; Lawless, Matthew W.; May, Jedediah H. (The Journal of Knee Surgery, 2019)
The use of tranexamic acid (TXA) in total knee arthroplasty (TKA) has become common practice. Recent literature has demonstrated a reduction in postoperative knee swelling and drain output while using TXA. Our purpose is to analyze the range of motion (ROM) following TKA in patients who received TXA compared with a control group. We hypothesize that patients treated with TXA will have improved early postoperative ROM when compared with controls. A retrospective chart review was performed for patients who underwent TKA from 2010 to 2012 performed by a single orthopaedic surgeon. Patients were stratified into three cohorts by route of TXA administration including intravenous (IV), topical, and a control group. Dependent variables analyzed included extension, flexion, and total arc ROM on each postoperative day (POD), average ROM across all three postoperative days, as well as pre-to-postoperative differences in ROM. Demographic data were recorded for each patient. A total of 174 patients were included for analysis, 75 controls and 99 receiving TXA. A significant difference was found between the treatment groups and the control for all variables (for each, p ≤ 0.002). There were no significant differences in ROM between the IV and topical TXA treatment groups (for each, p ≥ 0.558). A multivariate analysis demonstrated no significant difference between the groups in complication rate or demographic variables. The use of TXA may improve early postoperative ROM following TKA.
Keywords: tranexamic acid; total knee arthroplasty; postoperative range of motion